Pengembangan Buku Digital Berbasis Multiple Representasi Pada Materi Ikatan Kimia Sebagai Sumber Belajar Berbasis Digital Siswa SMA Kelas X - Rumondor, Desire; Akbar, Jakub Saddam; Howan, Dian Herlinda Octorina; Djakariah, Djakariah; Akbar, Ayu Febrianty (Chemistry Department, Universitas Negeri Manado, 2025)
This study aims to develop a digital textbook based on multiple representations on chemical bonding as a digital learning resource for 10th-grade high school students. Product development was conducted using the Research and Development (R&D) method with the ADDIE model. Product validation involved media experts, material experts, and field trials with students using a Likert scale questionnaire instrument of 1–5. The assessment results showed that the digital textbook received a